Energy Consumption Efficiency Behaviours and Attitudes among the Community - Bishoge, Obadia Kyetuza; Kombe, Godlisten Gladstone; Mvile , Benatus Norbert (International Journal of Sustainable Energy Planning and Management, 2021)
The world is currently experiencing a high demand for energy that leads to an increase in energy consumption. The increased energy consumption rate leads to a rise in greenhouse gas emissions which provide climate change concerns in our earth. To tackle increased environmental challenges, there is a need for adopting energy behaviours among society globally. This review provides an overview of the approaches, theories, and models which explain in detail how human behaviours can influence energy use and hence increase energy saving. It furthermore evaluates the factors that influence human behaviours and attitudes toward energy consumption. In this section, the discussion is based on motivation factors; costs and benefits; moral and normative concerns; environmental norms, knowledge and concerns; technology adoption concerns; contextual and habitual factors; and awareness. To achieve this, a comprehensive literature review followed by Seven-Step Model was conducted involving relevant studies related to the study topic.